Export Competitiveness Analysis of Indonesian Natural Rubber (HS 400122) Commodity in The Chinese Market - Kamala Nailil Muna; Ignatia Martha Hendrati (International Journal of Economics Development Research (IJEDR), 2023)
Natural rubber is a major industrial commodities of tropical crops that supports the national economy, espescially Indonesia. TSNR (Technically Specified Natural Rubber) is one of dominant products in the rubber exports market. This study is purposes to determine Indonesia’s level of competitiveness regarding TSNR exports and export performances of TSNR commodities in the Chinese market. Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), and Constant Market Share (CMS) are three methods of analyzing the competitiveness and market share of TSNR. Results indicated that Indonesia’s RCA is 13.99 where RCA is >1 and Indonesia’s RSCA is 0.84 where RSCA > 0, meaning Indonesian exports are competitive in the Chinese market. But despite that fact, Indonesia's natural rubber market share tends to be weak with the export growth value of -0.08, commodity composition effect of -0.003048, market distribution effect of -0.000282 and competitiveness effect of -703,959.